Content (Gestión y Gerencia, 2019)
CONTENTEditorial……………………………………………………………………….………......      iArticles VILLALOBOS, Aldrin y PÉREZ, Juan José Partial adaptation of the venezuelan company in an environment of regulations and controls. Periodo: 2010-2015………………………………………………………...……….…     1MENDOZA, YohanaThe positive and postpositive conception of science in the construction of contemporary management thinking …………………………………………………………...…...........…….   27SÁNCHEZ, Juan Carlos y VALDIVÉ, CarmenProximities when actuating epistemic-cognitive mathematics. Prelude that springs from testimonies of novice and expert mathematicians. An exploratory study………..………….   50FLORES, Leydi YohannaIdentification of organizational practices for the accumulation of knowledge and information management tools ………...……………………………………………..….…..….   87ZERPA, Saicidy; ROSALES, Maritza y MORALES, OdalisApplied accounting of the public and business sectors in Venezuela ….…………..………99        104SAENZ, José A.; CAMACHO, Leylan y MENDOZA, Gaudis A Hazard analysis and critical control point (haccp)  in a company balanced food for animals …….........................................…………………………………………....……..…..… 124PERNÍA, Juan CarlosTraining management in university centers under a values approach …….………..……… 152CALLES, JoséObstacles to achieve productive efficiency in venezuelan companies. Period: 2007-2015…………………........................................................................................................... 168Publication standards …………..……….…..……….………………….………….…...…….197